Digital Twin of a Hierarchical CO2 Electrolyzer Gas Diffusion Electrode. (20th December 2022) - McLaughlin, David; Bierling, Markus; Mayerhöfer, Britta; Schmid, Günter; Thiele, Simon
Abstract: The electrochemical reduction of CO2 provides a pathway to a sustainable carbon cycle, allowing for the production of hydrocarbons critical for both chemical industry and mobility. Major engineering challenges need to be met in order to achieve efficient and large‐scale CO2 electrolysis. One central challenge is to find the optimum structure for the gas diffusion electrode at the heart of the electrolyzer. An optimum structure will achieve higher conversion efficiencies, lifetime, and product selectivity at lower cost. Critical structural properties of the electrode span the scale from nanometers to millimeters. To rationalize the optimization process, it behooves us to obtain a fully resolved multi‐scale model of the electrode. This digital twin, produced by bridging scale and employing multiple imaging methods, enables the digital study, simulation, and modification of the structure of the electrode. The model is used to simulate the transport processes vital to the functioning of the electrode thus further advancing the digital twin. Subsequently, it is explored how changes to the structure affect the predicted transport properties. The digital twin presented is only supposed to be the kernel and will be complemented by numerous future works. Abstract : Using a combination of focused ion beam/scanning electron microscope tomography and X‐ray microtomography, the structure of a CO2 reduction reaction gas diffusion electrode is reproduced accurately. The 3D model allows for virtual analysis of the structure. Additionally, it can be used to predict transport properties of the electrode. Two digital modifications of the model are considered: compression and binder content addition.